Social Media-Based Triangular Fraud and Cyber Law Enforcement: An Indonesian Transnational Digital Crime Perspective - Rombe, Erica Natalia; Ilyas, Amir (Universitas Negeri Gorontalo, 2026)
This study examines law enforcement against triangular fraud on social media and the strategies adopted by the police to address this emerging form of cyber-enabled deception. The urgency of this research lies in the increasing use of social media as a platform for fraudulent transactions, where perpetrators manipulate buyers and sellers through a three-party scheme that obscures criminal responsibility and complicates evidence tracing. Unlike conventional online fraud, triangular fraud involves layered communication, false representation, and indirect transaction patterns, making it more difficult for law enforcement agencies to investigate and prosecute effectively. This study employs an empirical legal research method, using qualitative analysis presented descriptively based on field data and law enforcement practice. The findings reveal that law enforcement against triangular fraud remains suboptimal due to limited human resources, insufficient cybercrime expertise among police officers, and inadequate facilities for tracking digital evidence. The Makassar Police have responded through three main strategies: pre-emptive efforts by conducting public outreach and legal education, preventive efforts through investigation and inquiry, and repressive efforts aimed at raising public awareness and encouraging caution in online transactions. The novelty of this study lies in its specific focus on triangular fraud as a distinct modus operandi within social media-based cybercrime. Its contribution is to highlight the need for stronger cyber-investigative capacity, improved digital evidence infrastructure, and preventive public education as part of a more adaptive law enforcement model for digital fraud cases. Practical prevention measures include verifying sellers through video calls, documenting communication, and confirming live location before transaction.